Role of Islamic instruments in financing and reconstruction (Damascus University Journal for the economic and Political sciences, 2021)
This study deals with the role of Islamic instruments in economic development by channeling the funds collected after the closing of the subscription to development projects that the government is seeking to rehabilitate, develop or establish new projects.The first section dealt with the concept of Islamic instruments, the mechanism of issuing it and the characteristics that characterized it from the commercial papers used in conventional banks, and the risks they could face. The second section concerns the economic importance of the Islamic instruments, either to its original source or to investors, by stating the advantages of each instrument and the economic aspects in which this instruments can be invested in economic development. Financial market, expanding the stock base. The third requirement for Islamic instruments is as a source of confidence for individuals in attracting and pooling savings and employing them in development projects because of the characteristics that distinguish them from other traditional financing instruments. The fourth section for the role of instruments in the return of money smuggled from abroad, and attract new funds from abroad to support the national economy.
Keywords: Role of Islamic instruments in financing and reconstruction